Dampak Konversi Lahan Pertanian: Studi Kondisi Sosial Ekonomi Masyarakat Kecamatan Moncongloe Kabupaten Maros - Rusneni Ruslan; Siska Siska; Batara Surya (Journal of Urban Planning Studies, 2021)
The purpose of this study was to determine the conversion of working agricultural land as a determinant of decreasing agricultural land productivity in Moncongloe District, Maros Regency and to find out how much influence agricultural land conversion, land productivity, land use and spatial changes have on the socio-economic conditions of the community in Moncongloe District, Maros Regency. . This research uses quantitative research with a quantitative approach method. The analysis used in this study is to use statistical cross tabulation analysis and chi-square analysis. The main conclusion of this study is that the three factors of working agricultural land conversion as a determinant of the decline in agricultural land productivity in Moncongloe Lappara Village and Moncongloe Village, Moncongloe District, give an effect sorted based on the level of frequency and percentage and five factors that influence agricultural land conversion, agricultural land productivity. , land use and spatial changes to the socio-economic conditions of the community in Moncongloe Lappara Village and Moncongloe Village, Moncongloe District.